Phosphogypsum roadbed filler and preparation method thereof

By using curing agent and waterproofing components in the phosphogypsum roadbed material for modification, combined with preconditioning of fly ash, the problems of low strength and insufficient water stability of the phosphogypsum roadbed material are solved, and high strength and high water stability are achieved phosphogypsum roadbed fillers reduce production costs and reduce environmental pollution.

CN119263765APending Publication Date: 2025-01-07HUBEI UNIV OF ARTS & SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411583004.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The low strength and insufficient water stability of traditional phosphogypsum roadbed materials lead to roadbed settlement and environmental pollution problems, and the existing improved methods are complex and costly.

Method used

The phosphogypsum is modified with curing agent and waterproof components. The strength and water stability of the phosphogypsum are improved by mixing with fly ash and grinding, avoiding high-temperature calcination treatment, and using ferric chloride, silane coupling agent, and silicon. Components such as ketozirconium stearic acid waterproofing agent, polydimethylsiloxane and sodium dodecyl sulfonate form a waterproof membrane to enhance the anti-permeability of phosphogypsum.

Benefits of technology

The mechanical properties and water stability of phosphogypsum roadbed fillers were significantly improved. The unlimited compressive strength of 7d 7.53~7.81MPa, and the water stability coefficient was not less than 0.83, which reduced production costs and effectively utilized phosphogypsum waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses ardealite roadbed filler and a preparation method thereof, and belongs to the technical field of roadbed engineering. The preparation method comprises the following steps: S1, mixing ardealite and fly ash, braising, drying and grinding to obtain pre-conditioned ardealite; s2, mixing the pre-conditioned phosphogypsum obtained in the step S1 with a curing agent to obtain a first mixture; and adding the waterproof component, uniformly mixing, adding water, and stirring to obtain the phosphogypsum roadbed filler. The waterproof component is prepared from ferric chloride, a silane coupling agent KH-792, a silicone zirconium stearic acid waterproof agent, polydimethylsiloxane and sodium dodecyl sulfate; according to the invention, the ardealite is pre-conditioned, and then the ardealite is modified by adopting the waterproof component prepared from the curing agent and specific components, so that the mechanical property and the water stability of the ardealite roadbed material can be remarkably improved, the ardealite with low comprehensive utilization rate is applied to highway construction on a large scale, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of roadbed engineering, and particularly relates to a phosphogypsum roadbed filler and a preparation method thereof. Background Art

[0002] Subgrade fillers refer to road construction materials located below the road base, which bear the vehicle loads transmitted from the road surface during application and resist the erosion of various environmental factors (freeze-thaw, drying, aqueous solution penetration, etc.). Subgrade fillers should have good strength, water stability and durability. Traditional subgrade fillers include natural resources such as pebbles, crushed stones, gravel and clay. With the construction of large-scale transportation facilities in my country, natural resources such as sand and gravel are close to exhaustion, and the use of clay will destroy vegetation and planting land. Therefore, from the perspective of resource protection, ecological protection and environmental protection, it is urgent to find alternative materials for traditional subgrade fillers.

[0003] Phosphogypsum is a byproduct of the wet process of preparing phosphoric acid. Its main component is CaSO4·2H2O, and it also contains inorganic residual impurities, making it acidic. Since it will directly or indirectly cause encroachment and pollution to environmental resources, it can only be treated as a waste residue. At present, a large amount of phosphogypsum in my country can only be piled up in the open air. The random discharge and accumulation of phosphogypsum not only occupies a large amount of land, but also contains acidic and other harmful substances that easily pollute the surrounding environment. The treatment and utilization of phosphogypsum is imminent. The annual discharge of phosphogypsum in my country reaches more than 80 million tons, but the comprehensive utilization rate of phosphogypsum is unsatisfactory. At present, there have been studies on the application of phosphogypsum in highway construction, but there are the following problems in using phosphogypsum directly in roadbed materials: on the one hand, the strength of phosphogypsum is low, which will cause roadbed settlement and cause road damage; on the other hand, the water stability is insufficient, and the strength is significantly reduced after contact with water; this limits the feasibility of phosphogypsum as roadbed material.

[0004] In order to solve the above technical problems, Chinese patent CN111320446A discloses a high-strength self-waterproof phosphogypsum roadbed material, which uses modified phosphogypsum powder obtained by calcining the phosphogypsum raw material for preparing the phosphogypsum roadbed material, which can improve the waterproof performance of the phosphogypsum roadbed material; however, in this technical solution, the phosphogypsum needs to undergo relatively complex calcination, cooling, crushing, and slow setting treatment to obtain a high-strength self-waterproof roadbed material, which has high investment costs and complex processes, and calcination, crushing and other processes will also cause certain environmental pollution. Chinese patent CN201811268754.X discloses a preparation and application method of a modified phosphogypsum road material, which uses the effective components of a curing agent to form insoluble substances with heavy metal substances in phosphogypsum, thereby curing the heavy metal ions in the phosphogypsum to reduce the pollution of the phosphogypsum; however, the curing agent raw material cost of this technical solution is relatively high, and the production is relatively complex.

[0005] Therefore, it is of great significance to prepare a phosphogypsum roadbed filler with high strength and good water stability, to reduce the stock of phosphogypsum on a large scale, to solve the problem of environmental pollution caused by stacking, and to achieve multiple benefits such as environmental protection, resource conservation, green development and reduced investment. Summary of the invention

[0006] In view of the above shortcomings of the prior art, one of the purposes of the present invention is to provide a method for preparing a phosphogypsum roadbed filler, wherein the phosphogypsum is modified by a curing agent and a waterproof component to prepare a phosphogypsum roadbed filler with high strength and good water stability. The roadbed filler of the present invention uses phosphogypsum as the main material, which can not only absorb a large amount of solid waste phosphogypsum, but also has a simple process and does not require high-temperature calcination.

[0007] To achieve the above purpose, the specific technical solutions of the present invention are as follows:

[0008] A method for preparing phosphogypsum roadbed filler comprises the following steps:

[0009] S1. The phosphogypsum and fly ash are mixed, and the phosphogypsum is obtained by stewing, drying and grinding to obtain pre-conditioned phosphogypsum;

[0010] S2. The preconditioned phosphogypsum obtained in step S1 is mixed with a curing agent to obtain a first mixture; a waterproof component is then added, mixed evenly, and water is added to obtain the phosphogypsum roadbed filler;

[0011] The waterproof component comprises ferric chloride, silane coupling agent KH-792, silicone zirconium stearic acid waterproof agent, polydimethylsiloxane and sodium dodecyl sulfonate.

[0012] The present invention first mixes phosphogypsum and fly ash, and the hydration reaction between the two will generate water-hardening products such as calcium sulfonate and hydrated calcium silicate gel. The materials are further ground to make them evenly mixed and the reaction is more complete. The above operation can improve the pore structure of the conditioned mixture, improve its density and strength, and obtain pre-conditioned phosphogypsum with high density and high strength. Then the pre-conditioned phosphogypsum is mixed with a curing agent, and the curing agent is used to cement the phosphogypsum particles to improve the strength and anti-penetration ability of the roadbed filler; finally, it is mixed with a waterproof component. The waterproof component of the present invention can generate insoluble substances to block micropores on the one hand, and can form a hydrophobic diaphragm on the surface of the phosphogypsum on the other hand, wrapping the phosphogypsum to avoid contact between the phosphogypsum and external water. More importantly, the waterproof component of the present invention can penetrate into the interior of the phosphogypsum, and the synergistic effect between the components of the waterproof component can significantly improve the water stability of the phosphogypsum roadbed filler.

[0013] Preferably, the preparation method of the waterproof component has the following steps: mixing the polydimethylsiloxane and the silicone zirconium stearic acid waterproofing agent, adding the silane coupling agent KH-792 during the mixing process, and then stirring at 50-60°C for 2-4 hours, and then adding the ferric chloride and sodium dodecyl sulfate, and ultrasonically dispersing for 0.5-1 hour to obtain the waterproof component.

[0014] Preferably, the mass ratio of the ferric chloride, the silane coupling agent KH-792, the silicone zirconium stearic acid waterproofing agent, the polydimethylsiloxane and the sodium dodecyl sulfate is (3-4): (0.5-1): (3-4): (2-3): (0.5-1).

[0015] Preferably, the mass of the waterproof component is 0.05% to 0.2% of the mass of the pre-conditioned phosphogypsum.

[0016] Preferably, the fly ash is Class C high calcium fly ash with a calcium oxide content of 12 wt% to 15 wt%. Class C fly ash not only has volcanic ash properties, but also has certain gelling properties and hydraulic properties, and the high calcium oxide content can provide more calcium sources for hydration reactions.

[0017] Preferably, the mass ratio of the phosphogypsum to fly ash is (7-9):(1-3).

[0018] Preferably, the mass ratio of the pre-conditioned phosphogypsum to the curing agent is (8-9): (1-2).

[0019] Preferably, the curing agent includes ferroaluminate cement, slag powder and steel slag powder. Compared with silicate cement, the use of ferroaluminate cement as a curing agent can significantly improve the strength of the solidified body of phosphogypsum roadbed filler.

[0020] Preferably, the mass ratio of the ferroaluminate cement, slag powder and steel slag powder is (1-2):(6-8):(1-2).

[0021] Preferably, the preparation method of the curing agent is as follows: the slag powder and steel slag powder are mixed with melamine, and then the ferroaluminate cement is added after ball milling to obtain the curing agent. The present invention uses melamine to fully grind the slag powder and steel slag powder. Melamine can improve the grindability of the steel slag powder and stimulate the activity of the steel slag powder. Then, the melamine is mixed with the ferroaluminate cement. The obtained curing agent can greatly enhance the strength of the phosphogypsum roadbed filler.

[0022] Preferably, the mass of the melamine is 3% to 5% of the total mass of the slag powder and the steel slag powder.

[0023] Preferably, the main mineral component of the phosphogypsum is dihydrate gypsum, and the content of dihydrate gypsum in the phosphogypsum is 80 wt%~95wt%.

[0024] Another object of the present invention is to provide phosphogypsum roadbed filler prepared by the preparation method.

[0025] Compared with the prior art, the present invention is beneficial in that:

[0026] (1) The present invention first preconditions the phosphogypsum, and then uses a waterproof component prepared from a curing agent and specific ingredients to modify the phosphogypsum, which can significantly improve the mechanical properties and water stability of the phosphogypsum roadbed material.

[0027] (2) The phosphogypsum roadbed filler prepared by the preparation method of the present invention has excellent basic mechanical properties and water stability, with a 7d unconfined compressive strength of 7.53-7.81 MPa and a water stability coefficient of not less than 0.83.

[0028] (3) The present invention applies phosphogypsum with low comprehensive utilization rate to highway construction on a large scale, so that phosphogypsum waste can be reasonably utilized and production costs can be reduced. DETAILED DESCRIPTION

[0029] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The slag powder shall be granulated blast furnace slag powder of grade not lower than S95, and its main components shall be CaO, Al2O3 and SiO2; the calcium oxide content in Class C fly ash shall be 12wt%~15wt%; the main component of phosphogypsum shall be CaSO4·2H2O, its moisture content shall not exceed 20%, and the mass fraction of CaSO4·2H2O shall not be less than 80%.

[0031] Example 1

[0032] This embodiment provides a method for preparing phosphogypsum roadbed filler, comprising the following steps:

[0033] S1. The phosphogypsum and Class C fly ash are mixed evenly in a mass ratio of 8:2, and then the material is stuffed for 48 hours, and then dried at 55°C, and then ground and sieved through a 200-mesh sieve to obtain pre-conditioned phosphogypsum;

[0034] S2. Mix slag powder and steel slag powder in a mass ratio of 7:2, then add 4% of melamine to the total mass of slag powder and steel slag powder, and ball mill at a ball-to-material ratio of 1:1 and a rotation speed of 140 rpm until the specific surface area is less than 400m 2 / kg, then add ferroaluminate cement (the mass ratio of ferroaluminate cement to slag powder is 1:7) to obtain a curing agent for use;

[0035] Mix polydimethylsiloxane and silicone zirconium stearic acid waterproofing agent, add silane coupling agent KH-792 while stirring, continue stirring at 55°C for 3h after adding, then add ferric chloride and sodium dodecyl sulfate, and ultrasonically disperse for 30min to obtain waterproof components for use. Among them, the mass ratio of ferric chloride, silane coupling agent KH-792, silicone zirconium stearic acid waterproofing agent, polydimethylsiloxane and sodium dodecyl sulfate is 3.5:0.5:3.5:2.5:0.5.

[0036] S3. The pre-conditioned phosphogypsum obtained in step S1 and the curing agent obtained in step S2 are mixed in a mass ratio of 9:1 to obtain a first mixture; then the waterproof component obtained in step S2 is added, the mass of the waterproof component is 0.1% of the pre-conditioned phosphogypsum, dry-mixed evenly, and the phosphogypsum roadbed filler is obtained after adding water and mixing, and the quality standard of water addition is the optimal moisture content of the filler ±2%.

[0037] Example 2

[0038] This embodiment provides a method for preparing phosphogypsum roadbed filler, comprising the following steps:

[0039] S1. The phosphogypsum and Class C fly ash were mixed evenly in a mass ratio of 7:3, and then the material was stuffed for 36 hours, and then dried at 50°C, and then ground and sieved through a 200-mesh sieve to obtain pre-conditioned phosphogypsum;

[0040] S2. Mix slag powder and steel slag powder in a mass ratio of 6:2, then add melamine accounting for 5% of the total mass of slag powder and steel slag powder, and ball mill at a ball-to-material ratio of 1:1 and a rotation speed of 140 rpm until the specific surface area is less than 400m 2 / kg, and then add ferroaluminate cement (the mass ratio of ferroaluminate cement to slag powder is 2:6) to obtain a curing agent for use;

[0041] The polydimethylsiloxane and the silicone zirconium stearic acid waterproofing agent were mixed, and the silane coupling agent KH-792 was added while stirring. After the addition was completed, the stirring was continued for 4 hours at 50°C, and then ferric chloride and sodium dodecyl sulfate were added. After ultrasonic dispersion for 30 minutes, the waterproof component was obtained for use. Among them, the mass ratio of ferric chloride, silane coupling agent KH-792, silicone zirconium stearic acid waterproofing agent, polydimethylsiloxane and sodium dodecyl sulfate was 3:1:4:2:1.

[0042] S3. The pre-conditioned phosphogypsum obtained in step S1 and the curing agent obtained in step S2 are mixed in a mass ratio of 8:2 to obtain a first mixture; then the waterproof component obtained in step S2 is added, the mass of the waterproof component is 0.05% of the pre-conditioned phosphogypsum, dry-mixed evenly, and water is added to obtain the phosphogypsum roadbed filler, and the quality standard of water addition is the optimal moisture content of the filler ±2%.

[0043] Example 3

[0044] This embodiment provides a method for preparing phosphogypsum roadbed filler, comprising the following steps:

[0045] S1. The phosphogypsum and Class C fly ash were mixed evenly in a mass ratio of 9:1, and then stuffed for 72 hours, and then dried at 60°C, and then ground and sieved through a 200-mesh sieve to obtain pre-conditioned phosphogypsum;

[0046] S2. Mix slag powder and steel slag powder in a mass ratio of 8:1, then add melamine accounting for 3% of the total mass of slag powder and steel slag powder, and ball mill at a ball-to-material ratio of 1:1 and a rotation speed of 140 rpm until the specific surface area is less than 400m 2 / kg, then add ferroaluminate cement (the mass ratio of ferroaluminate cement to slag powder is 1:8) to obtain a curing agent for use;

[0047] Mix polydimethylsiloxane and silicone zirconium stearic acid waterproofing agent, add silane coupling agent KH-792 while stirring, continue stirring at 60°C for 2h after adding, then add ferric chloride and sodium dodecyl sulfate, and ultrasonically disperse for 30min to obtain waterproof components for use. Among them, the mass ratio of ferric chloride, silane coupling agent KH-792, silicone zirconium stearic acid waterproofing agent, polydimethylsiloxane and sodium dodecyl sulfate is 4:1:3:3:1.

[0048] S3. The pre-conditioned phosphogypsum obtained in step S1 and the curing agent obtained in step S2 are mixed in a mass ratio of 9:1 to obtain a first mixture; then the waterproof component obtained in step S2 is added, the mass of the waterproof component is 0.2% of the pre-conditioned phosphogypsum, dry-mixed evenly, and the phosphogypsum roadbed filler is obtained after adding water and mixing, and the quality standard of water addition is the optimal moisture content of the filler ±2%.

[0049] Comparative Example 1

[0050] The preparation method of the phosphogypsum roadbed filler of this comparative example comprises the following steps:

[0051] S1. Mix slag powder, Class C fly ash and steel slag powder in a mass ratio of 7:2:2, then add 4% of melamine to the total mass of slag powder, Class C fly ash and steel slag powder, and ball mill at a ball-to-material ratio of 1:1 and a rotation speed of 140 rpm until the specific surface area is less than 400m2 / kg, then add ferroaluminate cement (the mass ratio of ferroaluminate cement to slag powder is 1:7) to obtain a curing agent for use;

[0052] Mix polydimethylsiloxane and silicone zirconium stearic acid waterproofing agent, add silane coupling agent KH-792 while stirring, continue stirring at 55°C for 3h after adding, then add ferric chloride and sodium dodecyl sulfate, and ultrasonically disperse for 30min to obtain waterproof components for use. Among them, the mass ratio of ferric chloride, silane coupling agent KH-792, silicone zirconium stearic acid waterproofing agent, polydimethylsiloxane and sodium dodecyl sulfate is 3.5:0.5:3.5:2.5:0.5.

[0053] S2. Mix the phosphogypsum passed through a 200-mesh sieve with the curing agent obtained in step S1 at a mass ratio of 9:1 to obtain a first mixture; then add the waterproof component obtained in step S1, wherein the mass of the waterproof component is 0.1% of the pre-conditioned phosphogypsum, dry mix evenly, and add water to obtain the phosphogypsum roadbed filler. The quality standard of water addition is the optimal moisture content of the filler ±2%.

[0054] That is, compared with Example 1, the pre-conditioning step of phosphogypsum is omitted in this comparative example, and Class C fly ash is added to the curing agent.

[0055] Comparative Example 2

[0056] The preparation method of the phosphogypsum roadbed filler of this comparative example comprises the following steps:

[0057] S1. The phosphogypsum and Class C fly ash are mixed evenly in a mass ratio of 8:2, and then stuffed for 48 hours, and then dried at 55°C, and then ground and sieved through a 200-mesh sieve to obtain pre-conditioned phosphogypsum;

[0058] S2. The slag powder, steel slag powder and ferroaluminate cement were mixed in a mass ratio of 7:2:1 to obtain a curing agent for standby use;

[0059] Mix polydimethylsiloxane and silicone zirconium stearic acid waterproofing agent, add silane coupling agent KH-792 while stirring, continue stirring at 55°C for 3h after adding, then add ferric chloride and sodium dodecyl sulfate, and ultrasonically disperse for 30min to obtain waterproof components for use. Among them, the mass ratio of ferric chloride, silane coupling agent KH-792, silicone zirconium stearic acid waterproofing agent, polydimethylsiloxane and sodium dodecyl sulfate is 3.5:0.5:3.5:2.5:0.5.

[0060] S3. The pre-conditioned phosphogypsum obtained in step S1 and the curing agent obtained in step S2 are mixed in a mass ratio of 9:1 to obtain a first mixture; then the waterproof component obtained in step S2 is added, the mass of the waterproof component is 0.1% of the pre-conditioned phosphogypsum, dry-mixed evenly, and the phosphogypsum roadbed filler is obtained after adding water and mixing, and the quality standard of water addition is the optimal moisture content of the filler ±2%.

[0061] That is, compared with Example 1, this comparative example only mixes slag powder, steel slag powder and ferroaluminate cement as a curing agent.

[0062] Comparative Example 3

[0063] This comparative example is substantially the same as Example 1, except that ferroaluminate cement is replaced by silicate cement.

[0064] Comparative Example 4

[0065] This comparative example is basically the same as Example 1, except that the silicone zirconium stearic acid waterproofing agent is replaced by sodium methyl silicate.

[0066] Comparative Example 5

[0067] This comparative example is basically the same as Example 1, except that ferric chloride is omitted and the amount of silicone zirconium stearic acid waterproofing agent is increased accordingly.

[0068] Comparative Example 6

[0069] The preparation method of the phosphogypsum roadbed filler of this comparative example comprises the following steps:

[0070] S1. The phosphogypsum and Class C fly ash are mixed evenly in a mass ratio of 8:2, and then stuffed for 48 hours, and then dried at 55°C, and then ground and sieved through a 200-mesh sieve to obtain pre-conditioned phosphogypsum;

[0071] S2. Mix slag powder and steel slag powder in a mass ratio of 7:2, then add 4% of melamine to the total mass of slag powder and steel slag powder, and ball mill at a ball-to-material ratio of 1:1 and a rotation speed of 140 rpm until the specific surface area is less than 400m 2 / kg, then add ferroaluminate cement (the mass ratio of ferroaluminate cement to slag powder is 1:7) to obtain a curing agent for use;

[0072] Evenly mix ferric chloride, zirconium silicone stearic acid waterproofing agent and polydimethylsiloxane in a mass ratio of 3.5:3.5:2.5 to obtain a waterproof component for use.

[0073] S3. The pre-conditioned phosphogypsum obtained in step S1 and the curing agent obtained in step S2 are mixed in a mass ratio of 9:1 to obtain a first mixture; then the waterproof component obtained in step S2 is added, the mass of the waterproof component is 0.1% of the pre-conditioned phosphogypsum, dry-mixed evenly, and the phosphogypsum roadbed filler is obtained after adding water and mixing, and the quality standard of water addition is the optimal moisture content of the filler ±2%.

[0074] That is, compared with Example 1, this comparative example only mixes ferric chloride, silicone zirconium stearic acid waterproofing agent and polydimethylsiloxane as the waterproof component.

[0075] Test example

[0076] The phosphogypsum roadbed fillers of Examples 1 to 3 and Comparative Examples 1 to 6 were subjected to unconfined compression tests, as follows: According to JTG3441-2024 "Test Procedures for Stabilized Materials of Inorganic Binders for Highway Engineering", the phosphogypsum roadbed fillers were placed in a cylindrical mold with a diameter and height of 5 cm, and after being fully compacted, they were wrapped with plastic wrap and placed in a curing room (temperature of 20±2°C, relative humidity>95%) for curing, and demolded after 24 hours. Then, they were cured in the following two ways: ① Standard curing: After demolding, they were continued to be wrapped with plastic wrap and placed in a curing room for curing to the specified age, and immersed in water for 24 hours on the last day of the age; ② Immersion test: After demolding, they were immersed in water for curing to the specified age. Then, the unconfined compressive strength of the test block was measured using a fully automatic press. The 7d unconfined compressive strength results are shown in Table 1, where the water stability coefficient is the ratio of the unconfined compressive strength of the immersion test to the standard curing.

[0077]

[0078] From the results in Table 1, it can be seen that the 7d unconfined compressive strength of the phosphogypsum roadbed fillers of Examples 1 to 3 of the present invention under standard curing conditions is 7.53 to 7.81 MPa, and by comparing the compressive strength of the immersion test and the standard curing, it can be seen that the water stability coefficient of Examples 1 to 3 is high, indicating that their water stability performance is excellent.

[0079] By comparing Example 1 with Comparative Example 1, it can be seen that the present invention can improve the strength of the phosphogypsum roadbed filler by pre-conditioning the phosphogypsum with Class C fly ash. By comparing Example 1 with Comparative Example 2, it can be seen that the present invention can significantly improve the curing effect of the curing agent by mixing melamine with slag powder and steel slag powder, thereby improving the strength of the phosphogypsum roadbed filler. By comparing Example 1 with Comparative Example 3, it can be seen that the curing agent made of ferroaluminate cement in the present invention has a better curing effect on phosphogypsum, which can significantly improve the strength of the roadbed filler; in addition, the inventors found that ferroaluminate cement can significantly enhance the flexural strength of the roadbed filler. By comparing Example 1 with Comparative Examples 4 to 6, it can be seen that changing the raw materials or preparation method of the waterproof component of the present invention will reduce the water stability of the phosphogypsum roadbed filler. The possible reason is that under the preparation method of the present invention, the raw materials of the waterproof component can synergistically improve the water stability of the phosphogypsum roadbed filler.

[0080] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing phosphogypsum roadbed filler, characterized in that: The following steps are involved: S1. The phosphogypsum and fly ash are mixed, and the phosphogypsum is obtained by stewing, drying and grinding to obtain pre-conditioned phosphogypsum; S2. The pre-conditioned phosphogypsum obtained in step S1 is mixed with a curing agent to obtain a first mixture; a waterproof component is then added, mixed evenly, and water is added to obtain the phosphogypsum roadbed filler; The waterproof component comprises ferric chloride, silane coupling agent KH-792, silicone zirconium stearic acid waterproof agent, polydimethylsiloxane and sodium dodecyl sulfonate.

2. The method for preparing a phosphogypsum roadbed filler according to claim 1, characterized in that: The preparation method of the waterproof component has the following steps: mixing the polydimethylsiloxane and the silicone zirconium stearic acid waterproofing agent, adding the silane coupling agent KH-792 during the mixing process, and then stirring at 50-60° C. for 2-4 hours, and then adding the ferric chloride and sodium dodecyl sulfate, and ultrasonically dispersing for 0.5-1 hour to obtain the waterproof component.

3. The method for preparing a phosphogypsum roadbed filler according to claim 1, characterized in that: The mass ratio of ferric chloride, silane coupling agent KH-792, silicone zirconium stearic acid waterproofing agent, polydimethylsiloxane and sodium dodecyl sulfate is (3~4):(0.5~1):(3~4):(2~3):(0.5~1).

4. The method for preparing a phosphogypsum roadbed filler according to claim 1, characterized in that: The mass of the waterproof component is 0.05% to 0.2% of the mass of the pre-conditioned phosphogypsum.

5. The method for preparing a phosphogypsum roadbed filler according to claim 1, characterized in that: The fly ash is Class C fly ash, and the calcium oxide content is 12wt%-15wt%.

6. The method for preparing a phosphogypsum roadbed filler according to claim 1, characterized in that: The mass ratio of the phosphogypsum to fly ash is (7-9):(1-3).

7. The method for preparing a phosphogypsum roadbed filler according to claim 1, characterized in that: The curing agent includes ferroaluminate cement, slag powder and steel slag powder.

8. The method for preparing a phosphogypsum roadbed filler according to claim 7, characterized in that: The mass ratio of the ferroaluminate cement, slag powder and steel slag powder is (1-2):(6-8):(1-2).

9. The method for preparing a phosphogypsum roadbed filler according to claim 7, characterized in that: The preparation method of the curing agent is as follows: the slag powder and steel slag powder are mixed with melamine, ball-milled and then the ferroaluminate cement is added to obtain the curing agent.

10. The phosphogypsum roadbed filler prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation and application methods of modified phosphogypsum road materials based on aluminum smelting waste

    CN109369119B

  • High-strength self-waterproof phosphogypsum roadbed material and preparation method thereof

    CN111320446A